Structural and Biochemical Properties of Novel Self-Cleaving Ribozymes - Lee, Ki-Young (Molecules, 2017)
Fourteen well-defined ribozyme classes have been identified to date, among which nine are site-specific self-cleaving ribozymes. Very recently, small self-cleaving ribozymes have attracted renewed interest in their structure, biochemistry, and biological function since the discovery, during the last three years, of four novel ribozymes, termed twister, twister sister, pistol, and hatchet. In this review, we mainly address the structure, biochemistry, and catalytic mechanism of the novel ribozymes. They are characterized by distinct active site architectures and divergent, but similar, biochemical properties. The cleavage activities of the ribozymes are highly dependent upon divalent cations, pH, and base-specific mutations, which can cause changes in the nucleotide arrangement and/or electrostatic potential around the cleavage site. It is most likely that a guanine and adenine in close proximity of the cleavage site are involved in general acid-base catalysis. In addition, metal ions appear to play a structural rather than catalytic role although some of their crystal structures have shown a direct metal ion coordination to a non-bridging phosphate oxygen at the cleavage site. Collectively, the structural and biochemical data of the four newest ribozymes could contribute to advance our mechanistic understanding of how self-cleaving ribozymes accomplish their efficient site-specific RNA cleavages.